Re and 99m Tc tricarbonyl probes for target-specific detection of melanoma and sentinel lymph node - Morais, Maurício da Silva, 1978- (2013)
Tese de doutoramento, Química (Química Inorgânica), Universidade de Lisboa, Faculdade de Ciências, 2013